2011
DOI: 10.1037/a0025095
|View full text |Cite
|
Sign up to set email alerts
|

The effects of general and homophobic victimization on adolescents' psychosocial and educational concerns: The importance of intersecting identities and parent support.

Abstract: Many adolescents experience peer victimization, which often can be homophobic. Applying the minority stress model with attention to intersecting social identities, this study tested the effects of general and homophobic victimization on several educational outcomes through suicidality and school belonging among 15,923 adolescents in Grades 7 through 12 on account of their sexual orientation and race/ethnicity. Parent support also was tested as a moderator of these effects. Homophobic victimization had differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
204
3
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(230 citation statements)
references
References 65 publications
(104 reference statements)
12
204
3
11
Order By: Relevance
“…ethnicity, social class) are likely to impact upon experiences of homophobia and/or health and wellbeing (Fish, 2008;Phoenix, Frosh and Pattman, 2003;Poteat et al, 2011), an in-depth analysis of these factors was beyond the scope of this study. Further limitations are that participants (because the study sought to explore these very contexts)…”
Section: Participantsmentioning
confidence: 99%
“…ethnicity, social class) are likely to impact upon experiences of homophobia and/or health and wellbeing (Fish, 2008;Phoenix, Frosh and Pattman, 2003;Poteat et al, 2011), an in-depth analysis of these factors was beyond the scope of this study. Further limitations are that participants (because the study sought to explore these very contexts)…”
Section: Participantsmentioning
confidence: 99%
“…In the present study, a parent and a teacher were examined separately as a caring adult to see their effects. Previous research (Poteat et al, 2011) examining only parent support did not find its significantly moderating effect on the relationship between victimization and school belonging, with the exception of sexual minority students of color.…”
mentioning
confidence: 99%
“…However, limited attention has been given to whether experiences of victimization during adolescence are largely responsible for the elevated levels of social and emotional distress and health among sexual minority youth. In addition, there is a dearth of research considering the impact of victimization on school-related outcomes among sexual minority adolescents, particularly with regard to population-based samples, although a recent study in the United States (Poteat, Mereish, DiGiovanni, & Koenig, 2011) has suggested the association between experiences of victimization and self-reports of truancy and grades among sexual minority students. Extending this suggestion, the present study examined the impact of victimization on wider range of school-related outcomes, including educational aspiration and engagement.…”
mentioning
confidence: 99%
“…Agree Poteat et al (2011), many adolescents experience peer victimization, which often can be homophobic. Applying the minority stress model with attention to intersecting social identities, this study tested the effects of general and homophobic victimization on several educational outcomes through suicide and school belonging among 15,923 adolescents in Grades 7 through 12 on account of their sexual orientation and race/ ethnicity.…”
Section: Introductionmentioning
confidence: 99%